Axle Temperature Detecting System of New-generation High-speed EMUs CRH380C - ZHANG Wen-zhong; HA Da-lei; WANG Qian (机车电传动)
Based on axle temperature detecting system structure and principle of CRH5 & CRH3 EMUs, new-generation high-speed EMUs axle temperature detecting system was developed with DSP+FPGA control system. The system has the features such as high detecting precise, excellent anti-interference ability, reliability and stability etc, which satisfies high-speed requirement.